ANALYSIS TRANSLATION OF FIGURATIVE LANGUAGE IN THE NOVEL INFERNO BY DAN BROWN - Erfan Pahlefi; Evert Hilman (PROJECT (Professional Journal of English Education), 2023)
This study aimed to find out the translation methods used by translators in translating figurative language in the novel Inferno by Dan Brown, 2013. This research is based on Newmark's theory in the "Text Book of Translation" book, as well as several other theories such as Abrams, Chesterman, and Nababan have been used to find out the answer in the analyzing process. This descriptive analysis research took the data from novel Inferno by Dan Brown as the research material. The research results on 55 data consist of thirty six data use of word for word translation, which are metaphor (20 data), simile (10 data), personification (3 data), and hyperbole (3 data). And there is nineteen data use of literal translation, which are metaphor (7 data), simile (4 data), personification (2 data), and hyperbole (6 data). For the assessment of the quality of translation on 55 data shows a very high level of accuracy, only 5 data show less accuracy level, and 50 data indicate high accuracy level, high acceptability level, and high readability level.Â Keywords:Â  Figurative Language; Translation; Translation Assiment; Translation Method